"Confidence" problems and literacy coaching: How a suburban kindergarten divided "good" and "bad" teachers in the accountability shove-down. (June 2023) - Sherfinski, Melissa
This paper explores the context of a Kindergarten team in a suburban P-3 school in Wisconsin developing literacy coaching support. Facing recent neoliberal accountability reforms that have greatly expanded teacher competition, dismantled teachers' unions, and added the role of the coach to the school, "confidence" is an issue that the coach and teachers struggle with as they seek to improve minority student achievement. Using a case study design and feminist sociological framework highlighting emotional labour, the affective economy, and the psychosocial possibilities of the work of PierreBourdieu, this research examines professional capital as a form of educators' experience. Ultimately, we see that the landscape of power and emotions is complex as it divides "good" and "bad" White and middle-class teachers. Possibilities for extending the uses of feminist sociological theory in early childhood literacy are discussed.